2008
DOI: 10.1103/physreva.78.022502
|View full text |Cite
|
Sign up to set email alerts
|

Efficient discretization of the continuum through complex contour deformation

Abstract: Instances of discrete states coupled to continua are physically ubiquitous. Numerical simulations of such systems often rely on a discrete representation of the continuum by a large but finite set of discrete levels, or "pseudostates." In this paper, we develop a method based on the prior work of Kazansky to derive an efficient discrete representation of an arbitrary continuum. For several test cases, our method allows the simulation of non-Markovian decay dynamics with a far smaller set of pseudostates than p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…More generally, near a metal surface, Shenvi et al have suggested discretizing the electronic bath, and running SH on a large number of independent potential energy surfaces (PESs). [18][19][20] A nonequilibrium version of the Shenvi algorithm might be possible in the vein of Refs. 21-26. In a previous paper, 27 which we refer to as Paper II, we have analyzed an alternative approach based on a classical master equation (CME) that describes the dynamics of the AH impurity subsystem.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, near a metal surface, Shenvi et al have suggested discretizing the electronic bath, and running SH on a large number of independent potential energy surfaces (PESs). [18][19][20] A nonequilibrium version of the Shenvi algorithm might be possible in the vein of Refs. 21-26. In a previous paper, 27 which we refer to as Paper II, we have analyzed an alternative approach based on a classical master equation (CME) that describes the dynamics of the AH impurity subsystem.…”
Section: Introductionmentioning
confidence: 99%
“…Direct discretization strategies Let us consider the approach of Ref. 25 and rephrase the problem of discretizing the Hamiltonian as that of discretizing the integral in (5). The simplest approximation for an integral is obtained by using a trapezoidal integration rule…”
Section: Relation Of Different Discretization Strategiesmentioning
confidence: 99%
“…In general, however, the FSSH algorithm has usually been restricted to studying isolated molecules in solvents with only a handful of electronic states. 38,68 Thus far, the most important exception to this general rule was the pioneering "Independent Electron Surface Hopping (IESH)" model of Shenvi, Roy, and Tully, [39][40][41] who studied NO scattering off of a gold surface. Shenvi et al suggested discretizing a continuum of adiabatic electronic levels to simulate electronic friction in a metal; by running FSSH on a large number of electronic states, Shenvi et al were able to correctly describe vibrational relaxation of the NO molecule.…”
Section: Introductionmentioning
confidence: 99%